THE BEST SOLUTIONS FOR SPEAKING IMPROVEMENT PROCESS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In this article, you will be given some information and measures by which people face their learning process. In addition, you tackle your problems connected with speaking by mentioning ways and techniques.